Comparative Analysis of the Lignins of Cork from Quercus suber L. and Wood from Eucalyptus globulus L. by Dry Hydrogen Iodide Cleavage - Akim, L G; Cordeiro, N; Pascoal Neto, C; Gandini, A (Lignin: Historical, Biological, and Materials Perspectives, 1999)
Lignin from cork (Quercus suber L.) was isolated by two procedures: organosolv extraction and dioxane-water (9:1) extraction in presence of HCl. These lignins were characterized using a mild hydrogen iodide-cleavage method followed by 1H NMR and GPC analysis. The results were compared with those for eucalyptus lignins (Eucalyptus globulus) isolated by the same procedures. The method used provided syringyl/guaiacyl ratios for the linear parts of the macromolecules and the degrees of crosslinking. The prevalence of guaiacyl units was demonstrated for cork lignin. Syringyl units were found to be minor components and present mainly in the linear parts of macromolecules. p-Hydroxyphenyl units were mainly condensed. Cork lignin was found to be significantly more cross-linked than eucalyptus lignin.
doi:10.1021/bk-2000-0742.ch014
Keywords: cross-linking (PG); Eucalyptus globulus; Lignin; Quercus suber